Ethylene-based copolymer composition and application thereof

The ethylene-based copolymer composition, featuring a specific ethylene-α-olefin-non-conjugated polyene copolymer and modified polybutadiene with high anti-aging agent content, addresses the issue of poor adhesion to synthetic fibers in conventional ethylene copolymer compositions, resulting in improved adhesion and mechanical properties for industrial applications.

JP2025057981APending Publication Date: 2025-04-09MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023167862
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Conventional ethylene-α-olefin-non-conjugated polyene copolymers exhibit inferior adhesion to synthetic fibers compared to polar rubbers, and existing bonding methods struggle to achieve sufficient adhesion in ethylene copolymer compositions used in industrial applications.

Method used

An ethylene-based copolymer composition comprising an ethylene-α-olefin-non-conjugated polyene copolymer with specific structural requirements, modified polybutadiene, and a high content of anti-aging agents, which improves adhesiveness with fiber-containing layers while maintaining mechanical properties.

Benefits of technology

The composition achieves enhanced adhesion and maintains excellent mechanical properties in laminates, leading to improved productivity and performance in industrial applications such as industrial belts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025057981000001
    Figure 2025057981000001
Patent Text Reader

Abstract

To provide an ethylene-based copolymer composition which can improve productivity by improving adhesiveness to a layer containing a fiber material, has excellent adhesiveness to a layer containing a fiber material and can maintain the mechanical properties of the resulting laminate.SOLUTION: There is provided an ethylene-based copolymer composition which comprises an ethylene / α-olefin / nonconjugated polyene copolymer (L) containing ethylene [A], an α-olefin having 4 to 20 carbon atoms [B] and a nonconjugated polyene [C] and satisfying specific requirements and a modified polybutadiene [N], and contains more than 10 pts.mass and 20 pts.mass or less of an antioxidant based on 100 pts.mass of the copolymer (L).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ethylene-based copolymer composition, a laminate, and an industrial belt. [Background technology]

[0002] Ethylene-α-olefin-non-conjugated polyene copolymers such as ethylene-propylene-diene copolymer (EPDM) generally have excellent weather resistance, heat resistance, and ozone resistance, and are used in industrial automotive parts, industrial rubber products, electrical insulation materials, civil engineering and construction materials, rubberized fabrics, etc.

[0003] Conventional ethylene-α-olefin-non-conjugated polyene copolymers have the disadvantage of inferior adhesion to synthetic fibers compared to polar rubbers such as nitrile rubber, chloroprene rubber, and chlorosulfonated polyethylene. As a method for solving this disadvantage, it has been disclosed that the adhesion between ethylene-α-olefin-non-conjugated polyene copolymers and synthetic fibers is improved by using an adhesive solution of a chlorosulfonated copolymer (Patent Document 1).

[0004] However, in today's world where environmental issues such as non-halogenation are a concern, it is difficult to say that such adhesion technology that utilizes the polarity of halogenation is optimal. Also, as a conventional adhesion method, a method is known in which synthetic fibers are treated with resorcinol-formaldehyde-latex (RFL treatment), then embedded in rubber and crosslinked to adhere. More specifically, a method is known in which isocyanates or isocyanuric acid derivatives are used in the RFL treatment. However, even if these methods are applied to the case where an ethylene-based copolymer composition containing an ethylene-α-olefin-non-conjugated polyene copolymer is used as the rubber, it is difficult to obtain sufficient adhesion.

[0005] Also, in order to improve compression set resistance, it has been proposed to compound a sulfur-vulcanized ethylene propylene rubber compound in which zinc oxide made by compounding an ethylene-α-olefin-diene copolymer with trans-polyoctenylene rubber is compounded (Patent Document 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 42-23632 [Patent Document 2] Patent No. 2528033 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide an ethylene-based copolymer composition which can improve productivity by improving adhesion to a layer containing a fiber material, has excellent adhesion to a layer containing a fiber material, and can maintain the mechanical properties of the obtained laminate. [Means for solving the problem]

[0008] Means for Solving the Problems The present inventors have conducted intensive studies to solve the above-mentioned problems, and have found that the above-mentioned problems can be solved by an ethylene-based copolymer composition containing an ethylene-α-olefin-non-conjugated polyene copolymer (L) satisfying specific requirements and a modified polybutadiene (N), and containing an antioxidant in a specific amount, thereby completing the present invention.

[0009] That is, the present invention relates to, for example, the following [1] to

[11] . [1] The present invention comprises an ethylene-α-olefin-non-conjugated polyene copolymer (L) containing ethylene [A], an α-olefin having 4 to 20 carbon atoms [B], and a non-conjugated polyene [C], and a modified polybutadiene (N), which satisfy the following requirements (1) to (4): An ethylene-based copolymer composition comprising more than 10 parts by mass and not more than 20 parts by mass of an antioxidant per 100 parts by mass of the copolymer (L). (1) the molar ratio [[A] / [B]] of the structural unit derived from ethylene [A] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; (2) the content of the structural unit derived from the non-conjugated polyene [C] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from the above [A], [B] and [C]; (3) Mooney viscosity ML at 100°C (1+4) 100°C is 5 to 100; (4) The B value represented by the following formula (i) is 1.20 or more. B value=([EX]+2[Y]) / [2×[E]×([X]+[Y])]···(i) [Here, [E], [X] and [Y] respectively represent the mole fractions of ethylene [A], α-olefin [B] having 4 to 20 carbon atoms, and non-conjugated polyene [C], and [EX] represents the dyad chain fraction of ethylene [A]-α-olefin [B] having 4 to 20 carbon atoms.]

[0010] [2] The ethylene copolymer composition according to [1], wherein the α-olefin [B] having 4 to 20 carbon atoms is 1-butene.

[0011] [3] The ethylene copolymer composition according to [1] or [2], comprising 0.5 to 50 parts by mass of a modified polybutadiene (N) per 100 parts by mass of the ethylene-α-olefin-non-conjugated polyene copolymer (L).

[0012] [4] The ethylene copolymer composition according to any one of [1] to [3], further comprising a trans-polyoctenylene (M).

[0013] [5] The ethylene copolymer composition according to [4], comprising 0.5 to 50 parts by mass of trans-polyoctenylene (M) per 100 parts by mass of the ethylene-α-olefin-non-conjugated polyene copolymer (L).

[0014] [6] The ethylene copolymer composition according to any one of [1] to [5], further comprising an organic peroxide as a crosslinking agent.

[0015] [7] A laminate comprising a layer [I] made of the ethylene copolymer composition according to any one of [1] to [6] and a layer [II] containing a fiber material in contact with each other.

[0016] [8] The laminate according to [7], wherein the layer [I] is a layer formed by crosslinking the ethylene-based copolymer composition.

[0017] [9] The laminate according to [7] or [8], wherein the fiber material of the layer [II] contains a fiber treated with resorcinol-formaldehyde-latex.

[0018]

[10] The laminate according to any one of [7] to [9], wherein the fiber material of the layer [II] is canvas.

[0019]

[11] An industrial belt comprising the laminate according to any one of [7] to

[10] . Effect of the Invention

[0020] According to the present invention, it is possible to provide an ethylene-based copolymer composition that can improve productivity by improving adhesion to a layer containing a fiber material, and it is also possible to provide a laminate that has excellent adhesion between a layer made of the ethylene-based copolymer composition and a layer containing a fiber material and maintains good mechanical properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] <Ethylene-based copolymer composition> The ethylene-based copolymer composition of the present invention (hereinafter also referred to as the present composition) comprises an ethylene-α-olefin-non-conjugated polyene copolymer (L) and a modified polybutadiene (N), and is characterized in that it contains more than 10 parts by mass and not more than 20 parts by mass of an antioxidant per 100 parts by mass of the copolymer (L).

[0022] <Ethylene-α-olefin-non-conjugated polyene copolymer (L)> The ethylene-α-olefin-non-conjugated polyene copolymer (L), which is one of the components of the composition, contains structural units derived from ethylene [A], structural units derived from an α-olefin [B] having 4 to 20 carbon atoms, and structural units derived from a non-conjugated polyene [C], and satisfies the following requirements (1) to (4). Such a specific ethylene-α-olefin-non-conjugated polyene copolymer may be abbreviated as "ethylene-based copolymer (L)".

[0023] The α-olefin [B] having 4 to 20 carbon atoms and the non-conjugated polyene [C] may each be used alone or in combination of two or more kinds.

[0024] Requirement (1) The molar ratio [[A] / [B]] of the structural unit derived from ethylene [A] to the structural unit derived from an α-olefin [B] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. The ethylene copolymer (L) having a molar ratio within the above range has an excellent balance between rubber elasticity at low temperature and tensile strength at room temperature. The lower limit of [A] / [B] is preferably 50 / 50, more preferably 60 / 40, and even more preferably 65 / 35. The upper limit of [A] / [B] is preferably 85 / 15, more preferably 80 / 20, and even more preferably 75 / 25.

[0025] Requirement (2) The content of the structural units derived from the non-conjugated polyene [C] is 0.1 to 6.0 mol %, relative to 100 mol % of the total of the structural units derived from the ethylene [A], the structural units derived from the α-olefin [B] having 4 to 20 carbon atoms, and the structural units derived from the non-conjugated polyene [C]. The lower limit of the content of the structural unit derived from the non-conjugated polyene [C] is preferably 0.5 mol %. The upper limit of the content of the structural unit derived from the non-conjugated polyene [C] is preferably 4.0 mol %, more preferably 3.5 mol %, and further preferably 3.0 mol %. When the content of the structural unit derived from the non-conjugated polyene [C] is within the above range, the ethylene-based copolymer (L) has sufficient crosslinkability and flexibility.

[0026] Requirement (3) The ethylene copolymer (L) has a Mooney viscosity of ML at 100°C. (1+4) The temperature at 100°C is in the range of 5 to 150, preferably 10 to 60, and more preferably 20 to 40. When the Mooney viscosity at 100°C is within the above range, the ethylene-based copolymer (L) has excellent roll processability even in a high-hardness oil-less formulation, and also exhibits good post-treatment quality (ribbon handling properties) and has excellent rubber physical properties.

[0027] Requirement (4) The B value represented by the following formula (i) is 1.20 or more. B value=([EX]+2[Y]) / [2×[E]×([X]+[Y])]···(i) [Here, [E], [X] and [Y] respectively represent the mole fractions of ethylene [A], α-olefin [B] having 4 to 20 carbon atoms, and non-conjugated polyene [C], and [EX] represents the dyad chain fraction of ethylene [A]-α-olefin [B] having 4 to 20 carbon atoms.] The B value represented by the above formula (i) is preferably in the range of 1.20 to 1.80, and particularly preferably 1.22 to 1.40. When the B value is 1.20 or more, the compression set at low temperatures is small, and the ethylene copolymer (L) obtained has an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature.

[0028] Examples of the α-olefin [B] having 4 to 20 carbon atoms include 1-butene having 4 carbon atoms, 1-nonene having 9 carbon atoms, 1-decene having 10 carbon atoms, 1-nonadecene having 19 carbon atoms, and 1-eicosene having 20 carbon atoms, which have a linear structure without a side chain, as well as 4-methyl-1-pentene, 9-methyl-1-decene, 11-methyl-1-dodecene, and 12-ethyl-1-tetradecene, which have a side chain. Among these, α-olefins having 4 to 10 carbon atoms are preferred, 1-butene, 1-hexene, and 1-octene are more preferred, and 1-butene is particularly preferred.

[0029] Examples of the non-conjugated polyene [C] include linear non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene; cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, and 5-isopropylidene-2-norbornene. cyclic non-conjugated dienes such as bornene and 6-chloromethyl-5-isopropenyl-2-norbornene; and trienes such as 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,5-norbornadiene, 1,3,7-octatriene, 1,4,9-decatriene, 4,8-dimethyl-1,4,8-decatriene, and 4-ethylidene-8-methyl-1,7-nonadiene. Among these, linear non-conjugated dienes such as 1,4-hexadiene, and cyclic non-conjugated dienes such as 5-ethylidene-2-norbornene, 5-ethylidene-2-norbornene, and 5-vinyl-2-norbornene are preferred, cyclic non-conjugated dienes are more preferred, 5-ethylidene-2-norbornene and 5-vinyl-2-norbornene are further preferred, and 5-ethylidene-2-norbornene is particularly preferred.

[0030] Examples of the ethylene copolymer (L) include ethylene-1-butene-1,4-hexadiene copolymer, ethylene-1-pentene-1,4-hexadiene copolymer, ethylene-1-hexene-1,4-hexadiene copolymer, ethylene-1-heptene-1,4-hexadiene copolymer, ethylene-1-octene-1,4-hexadiene copolymer, ethylene-1-nonene-1,4-hexadiene copolymer, ethylene-1-decene-1,4-hexadiene copolymer, ethylene-1-butene-1,4-hexadiene copolymer, 1,4-Hexadiene copolymer, Ethylene-1-butene-5-ethylidene-2-norbornene copolymer, Ethylene-1-pentene-5-ethylidene-2-norbornene copolymer, Ethylene-1-hexene-5-ethylidene-2-norbornene copolymer, Ethylene-1-heptene-5-ethylidene-2-norbornene copolymer, Ethylene-1-octene-5-ethylidene-2-norbornene copolymer, Ethylene-1-nonene-5-ethylidene-2-norbornene copolymer, Ethylene-1-decene-5-ethylidene Ethylene-1-butene-1-octene-5-ethylidene-2-norbornene copolymer, Ethylene-1-butene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, Ethylene-1-pentene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, Ethylene-1-hexene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, Ethylene-1-heptene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer Examples of the ethylene copolymer (L) include ethylene-1-octene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, ethylene-1-nonene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, ethylene-1-decene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, and ethylene-1-butene-1-octene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer. One or more types of ethylene copolymer (L) are used as necessary.

[0031] Each of the ethylene copolymers (L) may contain at least one or more types of biomass-derived monomers (ethylene [A], α-olefin [B] having 4 to 20 carbon atoms, and non-conjugated polyene [C]). The same type of monomers constituting the polymer may be only biomass-derived monomers, may be only fossil fuel-derived monomers, or may contain both biomass-derived monomers and fossil fuel-derived monomers. The biomass-derived monomer is a monomer made from any renewable natural raw material or its residue, such as a plant-derived or animal-derived monomer, including fungi, yeast, algae, and bacteria, and contains as carbon 14 C isotope 1×10 -12 The biomass-derived monomer is contained in a ratio of about 100 (pMC) measured in accordance with ASTM D6866. The biomass-derived monomer can be obtained, for example, by a conventionally known method. It is preferable from the viewpoint of reducing the environmental load that the ethylene-based copolymer (L) contains a biomass-derived monomer. If the polymer production conditions such as the polymerization catalyst and polymerization temperature are the same, even if the raw material olefin is an ethylene-based polymer containing a biomass-derived olefin, 14 C isotope 1×10 -12 Other than the proportion of ethylene in the polymer, its molecular structure is the same as that of ethylene polymers made from fossil fuel-derived monomers. Therefore, its performance is said to be the same.

[0032] <Production method of ethylene-α-olefin-non-conjugated polyene copolymer (L)> The ethylene copolymer (L) can be obtained by various known production methods, for example, a conventionally known production method using a metallocene catalyst. For example, the metallocene catalyst and the production method using the catalyst can be adopted from the examples described in International Publication No. 2015 / 122415, particularly paragraphs

[0249] to

[0320] of the publication.

[0033] <Modified polybutadiene (N)> The modified polybutadiene (N), which is one of the components constituting the present composition, is a polybutadiene modified with an unsaturated carboxylic acid and / or a derivative thereof.

[0034] The present composition contains the modified polybutadiene (N) in addition to the ethylene copolymer (L). Therefore, the composition has good adhesion to other materials, for example, layers containing fibrous materials such as industrial belts, and a laminate obtained from the present composition has excellent adhesive strength between a layer formed by crosslinking the present composition and a layer containing a fibrous material.

[0035] Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, α-ethylacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, methyltetrahydrophthalic acid, and endo-cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid (Nadic Acid (trademark)). Derivatives of these include acid halides, amides, imides, acid anhydrides, and esters. Among these, unsaturated dicarboxylic acids and their acid anhydrides are preferred, maleic acid and maleic anhydride are more preferred, and maleic anhydride is particularly preferred.

[0036] Modified polybutadienes (N) are manufactured and sold by Cray Valley under the trade names of Ricon130MA8, Ricon130MA13, Ricon130MA20, Ricon131MA5, Ricon131MA10, Ricon131MA17, Ricon131MA18, Ricon131MA20, Ricon184MA6, etc.

[0037] The composition contains the modified polybutadiene (N) in an amount of preferably 0.5 to 50 parts by mass, more preferably 0.5 to 30 parts by mass, further preferably 0.5 to 10 parts by mass, and particularly preferably 0.5 to 7 parts by mass, per 100 parts by mass of the ethylene-α-olefin-non-conjugated polyene copolymer (L).

[0038] When the amount of modified polybutadiene (N) in the composition is within the above range, the composition has good adhesion to other materials, for example, layers containing fibrous materials such as industrial belts, and a laminate obtained from the composition has excellent adhesive strength between a layer formed by crosslinking the composition and a layer containing a fibrous material.

[0039] <Anti-aging agent (stabilizer)> The life of the seal packing formed from the composition can be extended by blending an antioxidant (stabilizer) with the composition. Examples of such antioxidants include conventionally known antioxidants, such as amine-based antioxidants, phenol-based antioxidants, and sulfur-based antioxidants.

[0040] Examples of the amine-based antiaging agents include aromatic secondary amine-based antiaging agents such as phenylbutylamine and N,N-di-2-naphthyl-p-phenylenediamine. Examples of phenol-based antioxidants include dibutylhydroxytoluene and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. Examples of sulfur-based anti-aging agents include thioether-based anti-aging agents such as bis[2-methyl-4-(3-n-alkylthiopropionyloxy)-5-t-butylphenyl]sulfide; dithiocarbamate-based anti-aging agents such as nickel dibutyldithiocarbamate; 2-mercaptobenzoylimidazole, 2-mercaptobenzimidazole, zinc salt of 2-mercaptobenzimidazole, dilaurylthiodipropionate, and distearylthiodipropionate.

[0041] The composition contains more than 10 parts by mass and not more than 20 parts by mass of an antioxidant based on 100 parts by mass of the ethylene copolymer (L). When the blending amount of the antioxidant in the present composition is within the above range, the composition has good adhesion to other materials, for example layers containing fiber materials such as industrial belts, and a laminate obtained from the present composition has excellent adhesive strength between a layer formed by crosslinking the present composition and a layer containing a fiber material. The blending amount of the antioxidant is preferably more than 10 parts by mass and not more than 15 parts by mass, more preferably 11 parts by mass or more and 13 parts by mass or less, based on 100 parts by mass of the ethylene copolymer (L). When the blend amount of the antioxidant in the present composition is within the above range, no bloom occurs on the surface of the obtained molded article, and furthermore, the occurrence of vulcanization inhibition can be suppressed.

[0042] <Trans polyoctenylene (M)> The present composition preferably contains trans-polyoctenylene (M). By containing trans-polyoctenylene (M), the present composition has good adhesion to other materials, for example, layers containing fibrous materials such as industrial belts, and a laminate obtained from the present composition has excellent adhesive strength between a layer formed by crosslinking the present composition and a layer containing a fibrous material. Trans polyoctenylene (M) is a polymer of octenylene having a trans structure, and is mainly a metathesis polymer of cyclooctene having a trans double bond (a polymer obtained by the metathesis polymerization method of trans double-bonded cyclooctene using a metal atom as a polymerization catalyst). Trans-polyoctenylene (M) is manufactured and sold by Evonik Industries under the trade name VESTENAMER.

[0043] When the present composition contains the trans polyoctenylene (M), the trans polyoctenylene (M) is preferably contained in an amount of 0.5 to 50 parts by mass, more preferably 1 to 30 parts by mass, further preferably 2 to 10 parts by mass, and particularly preferably 3 to 7 parts by mass. When the amount of trans-polyoctenylene (M) in the composition is within the above range, the composition has good adhesion to other materials, for example, layers containing fibrous materials such as industrial belts, and a laminate obtained from the composition has excellent adhesive strength between a layer formed by crosslinking the composition and a layer containing a fibrous material.

[0044] <Other ingredients> In addition to the above-mentioned components, the present composition may contain other components according to the desired purpose within the range that does not impair the effects of the present invention. The other components may contain at least one selected from, for example, a crosslinking agent, a crosslinking aid, a vulcanization accelerator, a vulcanization acceleration aid, a filler, a softener, a processing aid, an activator, a heat stabilizer, a weather stabilizer, an antistatic agent, a colorant, a lubricant, and a thickener. Each of the additives may be used alone or in combination of two or more kinds.

[0045] <Crosslinking Agent> Examples of the crosslinking agent include crosslinking agents generally used for crosslinking rubber, such as organic peroxides, phenolic resins, sulfur-based compounds, hydrosilicone-based compounds, amino resins, quinone or its derivatives, amine-based compounds, azo-based compounds, epoxy-based compounds, isocyanate-based compounds, and quinone dioxime-based crosslinking agents such as p-quinone dioxime. Among these, organic peroxides and sulfur-based compounds are preferred.

[0046] Examples of organic peroxides include dicumyl peroxide (DCP), di-tert-butyl peroxide, 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butyl peroxybenzoate, ert-butylperoxyisopropyl carbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide.

[0047] When an organic peroxide is used as a crosslinking agent, the amount of the organic peroxide in the composition is preferably 0.1 to 20 parts by mass, more preferably 0.2 to 15 parts by mass, and even more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the ethylene copolymer (L). When the amount of the organic peroxide is within the above range, no blooming occurs on the surface of the resulting molded article, and the composition exhibits excellent crosslinking properties.

[0048] When an organic peroxide is used as the crosslinking agent, it is preferable to use a crosslinking assistant in combination. The crosslinking auxiliary is a compound that acts as a crosslinking reaction catalyst when blended together with the crosslinking agent when the ethylene copolymer composition is crosslinked by heating. Examples of the crosslinking aid include acrylic crosslinking aids such as ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate; allyl crosslinking aids such as diallyl phthalate and triallyl isocyanurate; maleimide crosslinking aids; and divinylbenzene.

[0049] When a crosslinking auxiliary is used, the amount of the crosslinking auxiliary in the present composition is preferably 0.5 to 10 mol, more preferably 0.5 to 7 mol, and further preferably 1 to 6 mol, per mol of the organic peroxide.

[0050] When a sulfur-based compound is used as a crosslinking agent, examples of the compound include sulfur, sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, tetramethylthiuram disulfide, and selenium dithiocarbamate. Although sulfur is not a compound, it is classified as a sulfur-based compound in this specification for convenience.

[0051] When a sulfur-based compound is used as a crosslinking agent, the amount of the sulfur-based compound in the composition is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 7.0 parts by mass, and even more preferably 0.3 to 5.0 parts by mass, based on 100 parts by mass of the ethylene-based copolymer (L). When the amount of the sulfur-based compound is within the above range, no bloom occurs on the surface of the resulting molded article, and the composition exhibits excellent crosslinking properties.

[0052] When a sulfur-based compound is used as the crosslinking agent, it is preferable to use a vulcanization accelerator in combination. Examples of the vulcanization accelerator include N-cyclohexyl-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, N,N'-diisopropyl-2-benzothiazole sulfenamide, 2-mercaptobenzothiazole (e.g., Suncerer M (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), 2-(4-morpholinodithio)benzothiazole (e.g., Noccelaer MDB-P (trade name; manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)), 2-(2,4-dinitrophenyl)mercaptobenzothiazole, 2-(2,6-dinitrophenyl)mercaptobenzothiazole, Thiazole-based vulcanization accelerators such as ethyl-4-morpholinothio)benzothiazole and dibenzothiazyl disulfide (for example, Sancerer DM (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)); guanidine-based vulcanization accelerators such as diphenyl guanidine, triphenyl guanidine, and diorthotolyl guanidine; aldehyde amine-based vulcanization accelerators such as acetaldehyde-aniline condensation product and butyraldehyde-aniline condensation product; imidazoline-based vulcanization accelerators such as 2-mercaptoimidazoline; tetramethylthiuram monosulfide (for example, Sancerer DM (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)); thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (e.g., Sancerer TS (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetramethylthiuram disulfide (e.g., Sancerer TT (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetraethylthiuram disulfide (e.g., Sancerer TET (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetrabutylthiuram disulfide (e.g., Sancerer TBT (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), and dipentamethylenethiuram tetrasulfide (e.g., Sancerer TRA (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)); zinc dimethyldithiocarbamate, diethyldithio Examples of such vulcanization accelerators include dithioacid salt vulcanization accelerators such as zinc carbamate, zinc dibutyldithiocarbamate (e.g., Sancerar PZ, Sancerar BZ, and Sancerar EZ (trade names; manufactured by Sanshin Chemical Industry Co., Ltd.)) and tellurium diethyldithiocarbamate; thiourea vulcanization accelerators such as ethylenethiourea (e.g., Sancerar BUR (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.), Sancerar 22-C (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), N,N'-diethylthiourea, and N,N'-dibutylthiourea; and xanthate vulcanization accelerators such as zinc dibutylxatogenate.

[0053] When a vulcanization accelerator is used, the amount of the vulcanization accelerator in the present composition is preferably 0.1 to 20 parts by mass, more preferably 0.2 to 15 parts by mass, and further preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the ethylene copolymer (L). When the amount of the vulcanization accelerator is within the above range, no blooming occurs on the surface of the resulting molded article, and the composition exhibits excellent crosslinking properties.

[0054] When a sulfur-based compound is used as the crosslinking agent, the ethylene-based copolymer preferably contains a vulcanization accelerator.

[0055] Examples of the vulcanization accelerator include zinc oxide (e.g., ZnO#1 and zinc oxide type 2, manufactured by Hakusui Tech Co., Ltd.), magnesium oxide, and activated zinc oxide (e.g., zinc oxide such as "META-Z102" (trade name, manufactured by Inoue Seki Kogyo Co., Ltd.)). When a vulcanization acceleration aid is used, the blending amount of the vulcanization acceleration aid in the present composition is, for example, 1 to 20 parts by mass with respect to 100 parts by mass of the ethylene copolymer (L).

[0056] Filler The filler is a known rubber reinforcing agent that is compounded in the rubber composition, and is usually an inorganic substance called carbon black or an inorganic reinforcing agent.

[0057] Specific examples of the filler include Asahi #55G, Asahi #60UG, and Asahi #70 (all manufactured by Asahi Carbon Co., Ltd.), Seast (V, SO, 116, 3, 6, 9, SP, TA, etc.) carbon black (manufactured by Tokai Carbon Co., Ltd.), and these carbon blacks that have been surface-treated with a silane coupling agent or the like, as well as silica, activated calcium carbonate, finely divided talc, finely divided silicic acid, light calcium carbonate, heavy calcium carbonate, talc, and clay.

[0058] These fillers may be used alone or in combination of two or more. As the filler, preferably used are carbon black, silica, light calcium carbonate, heavy calcium carbonate, talc, clay, and the like.

[0059] When the composition contains a filler, the amount of the filler may be preferably 10 to 300 parts by mass, more preferably 20 to 200 parts by mass, further preferably 30 to 100 parts by mass, and particularly preferably 30 to 70 parts by mass, per 100 parts by mass of the ethylene copolymer (L). When the amount of the filler is within the above range, no blooming occurs on the surface of the resulting molded article, and the composition exhibits excellent crosslinking properties.

[0060] <Softener> Examples of softeners include petroleum-based softeners such as process oil, lubricating oil, paraffin oil, liquid paraffin, petroleum asphalt, and Vaseline; coal tar-based softeners such as coal tar; fatty oil-based softeners such as castor oil, linseed oil, rapeseed oil, soybean oil, and coconut oil; waxes such as beeswax and carnauba wax; naphthenic acid, pine oil, rosin or derivatives thereof; synthetic polymeric substances such as terpene resins, petroleum resins, and coumarone-indene resins; ester-based softeners such as dioctyl phthalate and dioctyl adipate; and others, such as microcrystalline wax, liquid polybutadiene, modified liquid polybutadiene, hydrocarbon-based synthetic lubricating oils, tall oil, and sub(factice). Of these, petroleum-based softeners are preferred, and process oil is particularly preferred.

[0061] When the present composition contains a softener, the blending amount of the softener is preferably 2 to 100 parts by mass, more preferably 3 to 50 parts by mass, further preferably 4 to 20 parts by mass, and particularly preferably 5 to 15 parts by mass, per 100 parts by mass of the ethylene-based copolymer (L).

[0062] <Processing aids> As the processing aid, a wide variety of processing aids that are generally compounded with rubber can be used.Specific examples include ricinoleic acid, stearic acid, palmitic acid, lauric acid, barium stearate, zinc stearate, calcium stearate, zinc laurate, and esters.Of these, stearic acid is preferred.

[0063] When the composition contains a processing aid, the amount thereof is preferably 0.1 to 20, more preferably 0.3 to 10, still more preferably 0.4 to 5, particularly preferably 0.5 to 3 parts by mass, per 100 parts by mass of the ethylene copolymer (L). When the blending amount of the processing aid is within the above range, excellent processability such as kneading processability, extrusion processability, and injection moldability is obtained, which is preferable.

[0064] <Activator> Examples of activators include amines such as di-n-butylamine, dicyclohexylamine, monoethanolamine, etc.; activators such as diethylene glycol, polyethylene glycol, lecithin, triallyl trimellitate, zinc compounds of aliphatic or aromatic carboxylic acids, etc.; zinc peroxide preparations; octadecyltrimethylammonium bromide, synthetic hydrotalcite, and special quaternary ammonium compounds.

[0065] When the present composition contains an activator, the amount of the activator is preferably 0.2 to 10 parts by mass, more preferably 0.3 to 5 parts by mass, based on 100 parts by mass of the ethylene copolymer (L).

[0066] <Preparation of Ethylene-Based Copolymer Composition> The present composition can be obtained by kneading the ethylene copolymer (L), the modified polybutadiene (N), an antioxidant, and, if necessary, the trans-polyoctenylene (M) and other components using a conventionally known kneading machine such as an internal mixer (internal mixer) such as a Banbury mixer, a kneader, or an Intermix, or a roll.

[0067] <Laminate> The laminate of the present invention is a laminate in which a layer [I] made of an ethylene copolymer composition is in contact with a layer [II] containing a fiber material. Each component of the laminate of the present invention will be described below.

[0068] <<Layer [I] made of ethylene-based copolymer composition>> In a preferred embodiment of the present invention, the layer [I] is a layer made of the above-mentioned ethylene-based copolymer composition, and is a layer obtained by crosslinking the above-mentioned ethylene-based copolymer composition.

[0069] <Layer containing fibrous material [II]> The layer [II] containing a fiber material constituting the laminate of the present invention contains a fiber material in at least a part of the layer.

[0070] <Textile materials> Examples of fiber materials for forming layer [II] include various known fiber materials, for example, natural fibers such as cotton and wood cellulose fibers; organic fiber materials such as fibers made of synthetic resins such as polyamide, polyester, polyvinyl alcohol, rayon, polyparaphenylene benzobisoxazole, polyethylene, polypropylene, polyarylate, polyimide, polyphenylene sulfide, polyether ether ketone, polylactic acid, polycaprolactone, polybutylene succinate, and fluorine-based polymers; and inorganic fiber materials such as glass fibers, PAN-based carbon fibers, pitch-based carbon fibers, alumina fibers, silicon carbide fibers, aluminum borate fibers, and potassium titanate whiskers.

[0071] These fiber materials may be long fibers (filaments) or short fibers (staples), and may be cord yarns, spun yarns, woven fabrics, knitted fabrics, canvas, nonwoven fabrics, and the like.

[0072] Examples of the polyamide include aliphatic polyamides such as nylon 6, nylon 6,6, and nylon 6,10; semi-aromatic polyamides such as polymetaxylylene adipamide (MXD6), polyhexamethylene terephthalamide (6T), and copolymer polyamides containing these units; and fully aromatic polyamides such as polybenzamide, poly-p-phenylene terephthalamide, and poly-m-phenylene isophthalamide.

[0073] Furthermore, these fiber materials may be surface-treated by a known method such as RFL treatment in order to improve adhesion between the fiber materials themselves or between the fiber materials and the layer [I] made of the present composition.

[0074] <RFL Processing> RFL treatment is a process in which textile materials are treated with a treatment liquid (RFL liquid) containing resorcinol, formalin, and latex, and this RFL liquid is a mixture of the initial condensation product of resorcinol and formalin and rubber latex. Examples of rubber latex that can be used include styrene-butadiene-vinylpyridine terpolymer (VP), styrene-butadiene copolymer (SBR), chloroprene (CR), acrylonitrile-butadiene copolymer (NBR), hydrogenated NBR (H-NBR), chlorosulfonated ethylene (CSM), and natural rubber. These can be used alone or in a blend of two or more types.

[0075] <Method of manufacturing laminate> To produce the laminate of the present invention, various known methods for producing laminates can be adopted. For example, a method of laminating a layer [I] made of an uncrosslinked ethylene copolymer composition previously molded by a known method with a layer [II] containing a fiber material, and then crosslinking the layer [I], a method of laminating a layer [I] previously crosslinked with a layer [II], or a method of extrusion coating the layer [I] on the layer [II], and then crosslinking the layer [I] can be mentioned.

[0076] Examples of methods for molding the uncrosslinked ethylene copolymer composition include methods of molding into a desired shape using a molding machine such as an extruder, a calendar roll, a press, an injection molding machine, or a transfer molding machine.

[0077] Simultaneously with or after the above-mentioned molding, the ethylene-based copolymer composition may be crosslinked to form a layer [I] made of this composition, and then laminated (bonded) with a layer [II] containing a fiber material. Alternatively, an uncrosslinked ethylene-based copolymer composition may be molded into a desired shape by the above-mentioned method, and then laminated (bonded) with a layer [II] containing a fiber material, and then the layer [I] is crosslinked.

[0078] The layer [I] made of the present composition may be crosslinked by either a method of heating using a crosslinking agent or a method of irradiating with light, gamma rays or electron beams. In addition, when crosslinking, a mold may be used, or crosslinking may be performed without using a mold. When a mold is not used, the molding and crosslinking steps are usually performed continuously. As a heating method in the crosslinking tank, a heating tank using hot air, a glass bead fluidized bed, UHF (ultra-high frequency electromagnetic waves), steam, etc. can be used.

[0079] <<Applications of the laminate>> The laminate of the present invention is suitably used for automobile hoses, water hoses, gas hoses, industrial belts such as transmission belts and conveyor belts, and escalator handrails.

[0080] Examples of the automotive hose include brake hoses, radiator hoses, heater hoses, and air cleaner hoses. Examples of the power transmission belt include a V-belt, a flat belt, and a toothed belt. Examples of the conveyor belt include a light conveyor belt, a cylindrical belt, a rough top belt, a conveyor belt with a flange, a conveyor belt with a U-shaped guide, and a conveyor belt with a V-shaped guide. EXAMPLES

[0081] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these.

[0082] The physical properties of each copolymer used in the following Examples and Comparative Examples were measured in the following manner. <Molar amount of each structural unit> The molar amounts of the structural units derived from ethylene [A], the structural units derived from α-olefin [B], and the structural units derived from non-conjugated polyene [C] are 1 The intensity was measured using a H-NMR spectrometer. Details of the measurement conditions are described in WO 2015 / 122415.

[0083] <Mooney Viscosity> Mooney Viscosity (ML (1+4) 100°C) was measured using a Mooney viscometer (Shimadzu Corporation, Model SMV202) in accordance with JIS K6300 (1994).

[0084] The measurement solvent was o-dichlorobenzene-d4 / benzene-d6 (4 / 1 [v / v]) at a measurement temperature of 120°C. 13 A C-NMR spectrum (100 MHz, JEOL ECX400P) was measured, and calculation was performed based on the following formula (i). B value = ([EX]+2[Y]) / [2×[E]×([X]+[Y])]...(i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A], α-olefins [B] having 4 to 20 carbon atoms, and non-conjugated polyenes [C], and [EX] represents the dyad chain fraction of ethylene [A]-α-olefins [B] having 4 to 20 carbon atoms.]

[0085] The ethylene / α-olefin / non-conjugated polyene copolymer (L) used in the examples of the present invention is shown below.

[0086] [Ethylene-α-olefin-non-conjugated polyene copolymer (L)] According to the description of [Synthesis Example C1] of WO 2015 / 122415, an ethylene-1-butene-5-ethylidene-2-norbornene (ENB) copolymer having the following physical properties was obtained. Hereinafter, this is referred to as "ethylene copolymer (L-1)". The composition and physical properties of the ethylene copolymer (L-1) are as follows: Structural units derived from ethylene: 67.7 mol% Structural units derived from 1-butene: 30.0 mol% Structural units derived from ENB: 2.3 mol% Structural units derived from ethylene / structural units derived from 1-butene [molar ratio]: 69 / 31 Mooney Viscosity ML (1+4) 100℃:30 B value: 1.3

[0087] The ethylene-α-olefin-non-conjugated polyene copolymers used in the comparative examples of the present invention are shown below.

[0088] [Ethylene-α-olefin-non-conjugated polyene copolymer (l)] As the ethylene-α-olefin-non-conjugated polyene copolymer (l), the following ethylene-propylene-ENB copolymer (ethylene-based copolymer (l-1)) was used. Ethylene-based copolymer (l-1) Product name Mitsui EPT 4045M: Mooney Viscosity ML (1+4) 100°C=45, ethylene content=45% by mass, diene (ENB) content=7.6% by mass

[0089] Example 1 The ethylene copolymer (L-1) was masticated for 30 seconds, and 100 parts by mass of the masticated ethylene copolymer (L-1) was mixed with 5 parts by mass of zinc oxide (ZnO#1) as a crosslinking aid, 1 part by mass of stearic acid as a lubricant, 4 parts by mass of Irganox 1010 (pentaerythritol tetrakis [3- (3,5-di-tert-butyl-4-hydroxyphenyl) propionate], manufactured by BASF) as an antiaging agent, 8 parts by mass of Sandant MB (2-mercaptobenzimidazole, manufactured by Sanshin Chemical Industry Co., Ltd.) as an antiaging agent, 50 parts by mass of Asahi #70 (manufactured by Asahi Carbon Co., Ltd.) as carbon black, and 10 parts by mass of Diana Process Oil PW-38 (manufactured by Idemitsu Kosan Co., Ltd.) as a softener, in a 1.7-liter Banbury mixer (manufactured by Kobe Steel, Ltd.) for 2 minutes. Thereafter, the ram was raised and cleaned, and kneading was further carried out for 1 minute, and the mixture was discharged at about 150° C. to obtain Blend 1. This kneading was carried out at a filling rate of 70%.

[0090] Next, 172 parts by mass of this compound was wound around an 8-inch roll (front roll surface temperature 50°C, rear roll surface temperature 50°C, front roll rotation speed 16 rpm, rear roll rotation speed 18 rpm), and 6.8 parts by mass of Mitsui DCP-40C (40% master batch, dicumyl peroxide, manufactured by Kayaku Akzo Co., Ltd.) as a crosslinking agent and 5 parts by mass of Ricon131MA18 (maleic anhydride modified polybutadiene, manufactured by Cray Valley Co., Ltd.) as a modified polybutadiene (N) were added and kneaded for 10 minutes to obtain Compound 2, which was then cut into sheets according to the test pieces to prepare uncrosslinked sheets with thicknesses of 1 mm, 2 mm, and 3 mm.

[0091] The adhesiveness (gf) of the obtained uncrosslinked sheet having a thickness of 1 mm was measured by the method described below. The results are shown in Table 1. The obtained uncrosslinked sheet having a thickness of 2 mm was pressed at 170° C. for 15 minutes using a 100-ton press molding machine to produce a crosslinked sheet. The physical properties of the obtained crosslinked sheet were measured by the methods described below. The results are shown in Table 1.

[0092] <Physical Properties of Ethylene-Based Copolymer Composition (Uncrosslinked)> <Measurement of Adhesion> The tackiness (Peak Value (gf)) was evaluated using a probe tack tester under the following conditions. 5mm diameter stainless steel probe Approach speed: 120mm / min Pressure: 100g Pressurization time: 20 seconds Peeling speed: 120mm / min Temperature at which the probe and test piece (uncrosslinked sheet) are placed: 50°C

[0093] <<Physical Properties of Crosslinked Ethylene-Based Copolymer Composition>> <Durometer A hardness> The hardness (Type A durometer, HA) of the crosslinked sheet was measured according to JIS K 6253 using six 2 mm thick crosslinked sheets with smooth surfaces, stacked on top of each other at the flat part to a thickness of approximately 12 mm. However, specimens with foreign matter, air bubbles, or scratches were not used. The dimensions of the measurement surface of the test specimen were set so that measurements could be made with the tip of the indenter at a position 12 mm or more away from the end of the test specimen.

[0094] <Tensile stress at break, tensile elongation at break> The tensile stress at break and the tensile elongation at break of the crosslinked sheet were measured by the following method. The crosslinked sheet was punched out to prepare No. 3 dumbbell test pieces described in JIS K 6251 (1993). Using these test pieces, tensile tests were performed according to the method specified in JIS K6251, section 3, at a measurement temperature of 25°C and a tensile speed of 500 mm / min to measure the tensile stress at break (TB) and tensile elongation at break (EB).

[0095] <Tear strength> In accordance with JIS K6252, an unnotched angle-shaped dumbbell test piece was prepared from a 2 mm thick crosslinked sheet, and this test piece was pulled at a tensile speed of 500 mm / min to measure the maximum stress value (tear strength) (measurement temperature: 25°C).

[0096] Peel strength The peel strength (adhesion strength) between the layer [I] made of the crosslinked ethylene copolymer composition and the layer [II] containing a fiber material was measured by the following method.

[0097] The uncrosslinked sheet having a thickness of 3 mm prepared above was placed on a woven fabric of nylon fiber subjected to RFL treatment [manufactured by Ayaha Kogyo Co., Ltd.], and the uncrosslinked sheet was crosslinked by pressing for 15 minutes at 170°C using a 200-ton press molding machine to obtain a laminate in which the layer [I] and the layer [II] are in contact with each other. A test piece having a width of 25 mm was punched out from the laminate, and a T-peel test was performed at a tensile speed of 50 mm / min to determine the peel strength (adhesive strength) (N / cm). The peel test was performed three times, and the average value was taken as the peel strength.

[0098] Example 2 Except for changing the blending amount of Asahi #70 to 40 parts by mass, and further blending 10 parts by mass of silica (product name ULTRASIL VN2, manufactured by Evonik) and 5 parts by mass of VESTENAMER 8012 (manufactured by Evonik) as trans-polyoctenylene (M), an uncrosslinked ethylene copolymer composition, a crosslinked ethylene copolymer composition and a laminate were obtained in the same manner as in Example 1, and the physical properties were evaluated by the methods described above. The results are shown in Table 1.

[0099] Comparative Example 1 An uncrosslinked ethylene copolymer composition was obtained in the same manner as in Example 1, except that the ethylene copolymer (l-1) was used instead of the ethylene copolymer (L-1) used in Example 1, and the amount of antioxidant (Irganox 1010 and Sandant MB) was changed to the amount shown in Table 1. Next, a crosslinked ethylene copolymer composition and a laminate were obtained in the same manner as in Example 1, except that sulfur and a vulcanization accelerator shown in Table 1 were used instead of DCP-40C and Ricon131MA18, and the physical properties were evaluated by the methods described above. The results are shown in Table 1.

[0100] Comparative Example 2 An uncrosslinked ethylene copolymer composition was obtained in the same manner as in Example 1, except that the blending amounts of the antioxidants (Irganox 1010 and Sandant MB) were changed to those shown in Table 1. Next, a crosslinked ethylene copolymer composition and a laminate were obtained in the same manner as in Example 1, except that Ricon131MA18 was not used, and the physical properties were evaluated by the methods described above. The results are shown in Table 1.

[0101] [Table 1]

[0102] As the vulcanization accelerators shown in Table 1 above, the following were used. Vulcanization accelerator TRA: Sancerer TRA (manufactured by Sanshin Chemical Industry Co., Ltd.) Vulcanization accelerator BZ: Sancerer BZ (manufactured by Sanshin Chemical Industry Co., Ltd.) Vulcanization accelerator 22: Sancerer 22-C (manufactured by Sanshin Chemical Industry Co., Ltd.) Vulcanization accelerator TT: Sancerer TT (manufactured by Sanshin Chemical Industry Co., Ltd.) Vulcanization accelerator M: Sancerer M (manufactured by Sanshin Chemical Industry Co., Ltd.)

[0103] As is clear from the results in Table 1, the results showed that the adhesiveness of the ethylene copolymer composition to the layer containing a fiber material in Examples 1 and 2 was superior to that of the compositions in Comparative Examples 1 and 2. In addition, the crosslinked ethylene copolymer compositions obtained in Examples 1 and 2 were excellent in mechanical properties. Furthermore, the laminates obtained in Examples 1 and 2 had very high peel strength values ​​compared to the laminates obtained in Comparative Examples 1 and 2, and were excellent in adhesiveness to the layer containing a fiber material.

Claims

1. The present invention comprises an ethylene / α-olefin / non-conjugated polyene copolymer (L) containing ethylene [A], an α-olefin [B] having 4 to 20 carbon atoms, and a non-conjugated polyene [C], and a modified polybutadiene (N), which satisfy the following requirements (1) to (4): An ethylene-based copolymer composition comprising more than 10 parts by mass and not more than 20 parts by mass of an antioxidant per 100 parts by mass of the copolymer (L). (1) the molar ratio [[A] / [B]] of the structural unit derived from ethylene [A] to the structural unit derived from an α-olefin [B] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; (2) the content of the structural unit derived from the non-conjugated polyene [C] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from the above [A], [B] and [C]; (3) Mooney viscosity ML at 100°C (1+4) 100°C is 5 to 100; (4) The B value represented by the following formula (i) is 1.20 or more. B value = ([EX]+2[Y]) / [2×[E]×([X]+[Y])]...(i) [Here, [E], [X] and [Y] respectively represent the molar fractions of ethylene [A], the α-olefin [B] having 4 to 20 carbon atoms, and the non-conjugated polyene [C], and [EX] represents the dyad chain fraction of ethylene [A]-α-olefin [B] having 4 to 20 carbon atoms.]

2. The ethylene copolymer composition according to claim 1, wherein the α-olefin [B] having 4 to 20 carbon atoms is 1-butene.

3. The ethylene-based copolymer composition according to claim 1, comprising 0.5 to 50 parts by mass of a modified polybutadiene (N) per 100 parts by mass of the ethylene / α-olefin / non-conjugated polyene copolymer (L).

4. The ethylene copolymer composition according to claim 1, further comprising a trans polyoctenylene (M).

5. The ethylene-based copolymer composition according to claim 4, comprising 0.5 to 50 parts by mass of trans-polyoctenylene (M) per 100 parts by mass of the ethylene / α-olefin / non-conjugated polyene copolymer (L).

6. The ethylene-based copolymer composition of claim 1, further comprising an organic peroxide as a crosslinking agent.

7. A laminate comprising a layer [I] made of the ethylene copolymer composition according to any one of claims 1 to 6 and a layer [II] containing a fiber material in contact with each other.

8. The laminate according to claim 7 , wherein the layer [I] is a layer formed by crosslinking the ethylene-based copolymer composition.

9. The laminate of claim 7, wherein the fibrous material of the layer [II] comprises resorcinol-formaldehyde latex-treated fibers.

10. The laminate according to claim 7, wherein the textile material of the layer [II] is canvas.

11. An industrial belt comprising the laminate of claim 7.

Citation Information

Patent Citations

  • JP1967-023632B

  • Ethylene propylene rubber compound

    JP2528033B2